The social ideal of “Datong”: ancient China social utopia, or modern foresight project - M. Yu. Zakharov (Вестник университета, 2022)
The subject of the study are features of the Chinese social ideal Datong and national specificity of its transformation into a modern Foresight project. To this end, universal characteristics of the ideal, common ground and differences of Datong existence historical forms – social ideal, social utopia, science fiction product have been considered in the article. Special attention has been paid to the understanding of the “Great Unity” concept as the very essence, indispensable element, basis for the development of the ideal Chinese society, ensuring its integrity and requiring a number of fundamental steps on the national level for its practical implementation. To solve modern grand socio-economic tasks, China needs not only a human being with a more perfect nature and good historical memory, but also the society potential in which all heterogeneous forces will be harmonically united. The results of the study extend the field of knowledge about Chinese culture for Russian audience.